Membangun Kreativitas Dan Jiwa Kewirausahaan Anak Panti Asuhan Melalui Kegiatan Meronce - Sinaga, Andry Marroan H; Dinda Rosanty; Herlita Andriani Sitohang; Elida Damai M. Parhusip; Lince Nora Yenny Barus; Norasi Wita Simanjuntak; Welrino Sitinjak; Teguh Satria Amin; Nurhafni Siregar (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
In the era of globalization and rapid technological development, developing creativity and an entrepreneurial spirit is becoming increasingly important, especially for children in orphanages. This article discusses a leadership project carried out by a student group from Nusantara Muslim University which aims to increase creativity and build an entrepreneurial spirit in the children of the Sendoro Orphanage in Medan. This project uses meronce activities as a medium to develop fine motor skills, creativity and basic understanding of entrepreneurship. Through this project, it is hoped that orphanage children can gain useful skills for their future and increase their self-confidence and independence.